Investigation on the flow limitation during copper electroplating of polyurethane foam - Katayoun Mohammadi; Mehdi Divandari; Saeed G. Shabestari (Journal of Materials Research and Technology, 2021)
The electroplating method was employed to precipitate ionic Cu on the polymeric foam substrate. To compare the effective parameters in the foam electroplating process, open-cell polyurethane foams with different pore sizes 30, 35, 40, and 70 ppi (pore per inch) were used. To attain the desired conductivity in polymeric foams, graphite was selected as a pre-coating material. Both direct current and pulsed current were used for electroplating samples. The results show that by reducing the pore size of the foams, significant changes in the ions' hydrodynamic behavior and forces from the electromagnetic field occur. These factors cause the trend of a coating rate to decrease. The magnitude of these changes in the sample with 70 ppi is more severe than in the other samples. It was seen that the precipitated Cu on the foam through the pulsed current electroplating method was smoother than its counterpart produced by a direct current electroplating method. Flower-shaped precipitations were observed in SEM images showing the nucleation and grain growth process. A physical model has described the precipitation mechanism according to the limiting diffusion current (LDC).